Renal Physiological Adaptation to High Altitude: A Systematic Review - Palubiski, Lisa M.; O'Halloran, Ken D.; O'Neill, Julie (Frontiers in Physiology, 2020)
Background: Under normal physiological conditions, renal tissue oxygen is tightly regulated. At high altitude, a physiological challenge is imposed by the decrease in atmospheric oxygen. At the level of the kidney, the physiological adaptation to high altitude is poorly understood, which might relate to different integrated responses to hypoxia over different time domains of exposure. Thus, this systematic review sought to examine the renal physiological adaptation to high altitude in the context of the extent and duration of exposure to high altitude in the healthy kidney model. Methods: To conduct the review, three electronic databases were examined: OVID, PubMed, and Scopus. Search terms included: Altitude, renal, and kidney. The broad, but comprehensive search, retrieved 1057 articles published between 1997 and April 2020. Fourteen studies were included in the review. Results: The inconsistent effect of high altitude on renal hemodynamic parameters (glomerular filtration rate, renal blood flow, and renal plasma flow), electrolyte balance, and renal tissue oxygen is difficult to interpret; however, the data suggest that the nature and extent of renal physiological adaptation at high altitude appears to be related to the magnitude and duration of the exposure. Conclusion: It is clear that renal physiological adaptation to high altitude is a complex process that is not yet fully understood. Further research is needed to better understand the renal physiological adaptation to hypoxia and how renal oxygen homeostasis and metabolism is defended during exposure to high altitude and affected as a long-term consequence of renal adaptation at high altitude.